Sistem Pakar Penanganan Jaringan Komputer Berbasis Delphi - Bagus Dwi Cahyono; Amar Jatnika; Irwanto Irwanto (Jurnal Pendidikan dan Pembelajaran, 2022)
Learning computer network material, especially computer network damage diagnosis material, is an abstract and difficult material to understand. The main objective of this research is to develop learning media that utilizes an expert system based on Borland Delphi 7 on valid computer network damage diagnosis material. This research was conducted in August 2021 at SMK 2 Serang. This learning media development design follows the ADDIE (Analyze, Design, Development, Implementation, Evaluation) stage. The validation of this learning media program includes content validation and the design of the media itself. Based on the results of data analysis, it was found that the learning media developed in this study had a very high validity value from the two aspects assessed. For the validity of this learning media subject matter, the validation by the expert is 3.61 and the validation by the teacher is 3.6 so it is very relevant to the concepts that will be taught using this media, while the validity of the media design by the expert is 3.5 and by the teacher 3.62 so that the learning media This research can be declared suitable to be used to support learning in schools